MEDICATION ERRORS: A REVIEWA - Agrawal, Dilip; Singh, Surya Pratap; Sharma, Bhupendra; Khinchi, Mahaveer Prasad; Sharmaq, Natasha (Asian Journal of Pharmaceutical Research and Development, 2013)
A recent report by the institute of Medicine estimated that as many as 98,000 people die in any given year from medical errors in hospitals alone. Medication errors, broadly defined as any error in the prescribing, dispensing, or administration of a drug, irrespective of whether such errors lead to adverse consequences or not, are the single most preventable cause of patient harm.The majority of medication errors occur as a result of poor prescribing and often involve relatively inexperienced medical staff, who are responsible for the majority of prescribing in hospital. The purpose of this paper is to review components of the medication use process and offer suggestions for transforming it into a safer system. Prevention strategies are suggested for improving medication use at each stage of the system. Decision criteria are proposed that can be used by administrators and healthcare providers to allocate resources for prevention strategies that will improve patient safety.